Pengolahan Makanan Sehat Berupa Nugget Sayur sebagai Upaya Pengentasan Stunting pada Balita - Misdawita, Misdawita; Manalu, Wina Indy Natasya; Sormin, Putri Adytia Dermawan; Purba, Kristina; Handayanti, Rani (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Stunting is still a big problem in Indonesia, including Riau Province. One way to prevent stunting is to improve nutrition by eating healthy and nutrient-rich foods such as vegetables. The purpose of this service is to provide information and knowledge to the public about stunting so that people are more aware of the dangers of stunting, and can increase the skills of the community, especially mothers, to be able to process vegetables into food that is attractive to children. The method used in this activity is to provide information to the public about stunting reduction and recipes for processing vegetable nuggets in the form of posters and provide training in making vegetable nuggets through educational videos on YouTube. The target in this study were mothers who had babies and toddlers in Tanjung Rhu Village, Limapuluh District, Pekanbaru City, Riau Province, namely 30 people. The results that have been achieved from this activity are increasing the knowledge and skills of mothers in making vegetable nuggets up to 95%. With this activity, parents who have toddlers gain new skills in modifying healthy food into attractive food for children so that children no longer refuse to eat nutritious food.